Pengambangan E-Modul Pembelajaran Perancangan Gambar dan Teknik Manufaktur Siswa Kelas XI Program Keahlian Teknik Fabrikasi Logam dan Manufaktur SMK N 1 Seyegan: Pengambangan E-Modul Pembelajaran Perancangan Gambar dan Teknik Manufaktur Siswa Kelas XI Program Keahlian Teknik Fabrikasi Logam dan Manufaktur SMK N 1 Seyegan - Ronald Hendrawan (JURNAL VOKASI DEWANTARA (JVD), 2023)
Today’s rapid technological development demands appropriate learning changes for students, especially in the subject of drawing design and manufacturing engineering training in Vocational High School (SMK). Vocational School in technology and industry groups are required to have quality skills and be able to compete in the world of work. In achieving goals and adapting to the times, teachers need to provide guidance with teaching materials that are much more effective and practical. This tesearch is a development research (R&D) by developing an e-module of drawing design and manufacturing techniques at SMK N 1 Seyegan. The assessment of the feasibility level of this e-module include material aspects from expert lecturers, teachers and media aspects as well as trials. The results of this e-module development research obtained feasibility results with a percentage of 79.38% and are in good classification with an average statistic of 3.18.